2022
DOI: 10.1155/2022/6203817
|View full text |Cite|
|
Sign up to set email alerts
|

Prophylactic Use of Antibiotics for Postsurgical Infection in c-TACE and DEB-TACE High-Risk Patients: A Case-Control Study

Abstract: Objectives. According to recent reports, prophylactic use of antibiotics is not always required in conventional transarterial chemoembolization (c-TACE). However, clinical evidence of prophylactic antibiotics in drug-eluting beads transarterial chemoembolization (DEB-TACE) to prevent postsurgical infection is limited. This study is aimed to evaluate the correlation between the preoperative prophylactic application of antibiotics and postoperative infection in c-TACE or DEB-TACE, especially in a population with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…In the hepatologist survey, 49.1% of the respondents used prophylactic antibiotics for all or selected cases. Although small retrospective studies showed negative results, 26 , 27 a recent large-scale cohort with propensity score analysis demonstrated that prophylactic antibiotics reduced the occurrence of liver abscess following TACE by two-thirds. 28 …”
Section: Prophylactic Medications For Infection and Postembolization ...mentioning
confidence: 99%
“…In the hepatologist survey, 49.1% of the respondents used prophylactic antibiotics for all or selected cases. Although small retrospective studies showed negative results, 26 , 27 a recent large-scale cohort with propensity score analysis demonstrated that prophylactic antibiotics reduced the occurrence of liver abscess following TACE by two-thirds. 28 …”
Section: Prophylactic Medications For Infection and Postembolization ...mentioning
confidence: 99%
“…In the hepatologist survey, 49.1% of the respondents used prophylactic antibiotics for all or selected cases. Although small retrospective studies showed negative results, 26,27 a recent large-scale cohort with propensity score analysis demonstrated that prophylactic antibiotics reduced the occurrence of liver abscess following TACE by two-thirds. 28 As the risk of liver abscess increases in cases of biliary obstruction, bilioenteric anastomosis, and biliary stent across the ampulla of Vater, 22,24 prophylactic antibiotics can be considered in patients with these biliary risk factors.…”
Section: Prophylactic Antibioticsmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%